2016
DOI: 10.1021/acsami.6b04418
|View full text |Cite
|
Sign up to set email alerts
|

Modified Separator Using Thin Carbon Layer Obtained from Its Cathode for Advanced Lithium Sulfur Batteries

Abstract: The realization of a practical lithium sulfur battery system, despite its high theoretical specific capacity, is severely limited by fast capacity decay, which is mainly attributed to polysulfide dissolution and shuttle effect. To address this issue, we designed a thin cathode inactive material interlayer modified separator to block polysulfides. There are two advantages for this strategy. First, the coating material totally comes from the cathode, thus avoids the additional weights involved. Second, the catho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The PP substrate was flexible and insulating; while CGFs had extraordinary electrical conductivity (100 S cm −1 ), high surface area (2120 m 2 g −1 ), and exceptional mesopore volume (3.1 cm 3 g −1 ), serving as an ideal building block for constructing reactivation layer. We found that coating the same amount of CGFs on the separator was much more efficient than mixing them in the cathode, which Liu et al also experimentally verified . Only 0.3 mg cm −2 coating of CGF on the separator significantly boosted the capacity and cycling stability of a double‐high sulfur cathode with sulfur content of 80 wt% in the slurry (68 wt% in the whole cathode with a CNT current collector) and an areal sulfur loading of 5.3 mg cm −2 .…”
Section: Separatorsupporting
confidence: 64%
“…The PP substrate was flexible and insulating; while CGFs had extraordinary electrical conductivity (100 S cm −1 ), high surface area (2120 m 2 g −1 ), and exceptional mesopore volume (3.1 cm 3 g −1 ), serving as an ideal building block for constructing reactivation layer. We found that coating the same amount of CGFs on the separator was much more efficient than mixing them in the cathode, which Liu et al also experimentally verified . Only 0.3 mg cm −2 coating of CGF on the separator significantly boosted the capacity and cycling stability of a double‐high sulfur cathode with sulfur content of 80 wt% in the slurry (68 wt% in the whole cathode with a CNT current collector) and an areal sulfur loading of 5.3 mg cm −2 .…”
Section: Separatorsupporting
confidence: 64%
“…Recently, the researchers have demonstrated that configuring the interlayer between the separator and sulfur cathode is an effective way to alleviate the "shuttle effect" in Li-S redox system. [38][39][40][41][42] To avoid the heavy and large volume of the free-standing interlayer, people have begun to modify the separator with functional materials, such as structural carbon materials [43][44][45][46][47][48] and metal-based compounds. [49,50] As the typical earthabundant, low-cost, and environmentally friendly materials, iron-based compounds have already been widely researched in Li-S batteries.…”
mentioning
confidence: 99%
“…Early in 2008, Huang et al showed that the gelatin not only functioned as a highly adhesive agent, but also acted as an effective dispersion agent for the cathode materials enhancing the redox reactions of sulfur cathode [64] . A following research demonstrated that the water-soluble gelatin increased the wetting ability of electrode by the electrolyte because of the rich -COOH and -NH 3 groups which also chemically bonded with LiPSs to suppress their shuttling, consequently improving the performance of Li-S batteries [65] . Another water-soluble natural binder, SA ( Fig.…”
Section: Natural Polymer Bindersmentioning
confidence: 99%